Peran Penting Keluarga dalam Perkembangan Sosioemosional pada Anak Usia Dini - Alsya Fitri; Fauziah Nasution; M. Maulana (Jurnal Dirosah Islamiyah, 2023)
Every child experiences development in his life according to his age. The success of children in achieving developmental goals is supported by several internal and external factors, including parenting style factors, family roles and functions, support from the environment outside the home and school and so on. Early childhood is the most rapid period of child development, especially in terms of socio-emotional development. This period is usually considered the golden period, which is the most valuable age compared to other ages. Therefore the role of the family, especially parents is very decisive. In this period, a character can grow because it receives the right motivation, and similarly if the motivation given is bad it will also create bad traits, because during this period a spontaneous attitude develops which cannot distinguish between good and bad attitudes. Keywords: Family; Socioemotional Development; Early Childhood